2021
DOI: 10.1101/2021.05.01.442157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aplp1 and the Aplp1-Lag3 Complex facilitates transmission of pathologic α-synuclein

Abstract: Pathologic alpha-synuclein (alpha-syn) spreads from cell-to-cell, in part, through binding to the lymphocyte-activation gene 3 (Lag3). Here we report that amyloid beta precursor-like protein 1 (Aplp1) forms a complex with Lag3 that facilitates the binding, internalization, transmission, and toxicity of pathologic alpha-syn. Deletion of both Aplp1 and Lag3 eliminates the loss of dopaminergic neurons and the accompanying behavioral deficits induced by alpha-syn preformed fibrils (PFF). Anti-Lag3 prevents the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Cell-surface receptors including LAG3 and amyloid precursorlike protein 1 (APLP1) have been reported to bind a-syn fibrils to mediate their cell-to-cell transmission in PD (Mao et al, 2016(Mao et al, , 2021Gu et al, 2021;Zhang et al, 2021). LAG3 and APLP1 share a common mechanism of charge interactions to bind a-syn (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-surface receptors including LAG3 and amyloid precursorlike protein 1 (APLP1) have been reported to bind a-syn fibrils to mediate their cell-to-cell transmission in PD (Mao et al, 2016(Mao et al, , 2021Gu et al, 2021;Zhang et al, 2021). LAG3 and APLP1 share a common mechanism of charge interactions to bind a-syn (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte activation gene 3 (LAG3) is a protein receptor on cell surface that has been reported to mediate the cell-to-cell transmission of pathologic a-syn aggregates (Mao et al, 2016(Mao et al, , 2021Gu et al, 2021). Our previous work has revealed that the interaction between LAG3 and a-syn fibrils is via the charge interactions between the domain 1 of LAG3 (L3D1) and the C-terminal residues of a-syn (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focus on using AAV-PFFNB2 to target intracellular α-syn aggregates against pathogenic α-syn spreading. Of note, emerging evidence also suggests the importance of exogenous α-syn aggregates in α-syn cell-to-cell transmission, by entering neurons and seeding endogenous α-syn aggregation 12,70,71 . Encouragingly, two α-syn antibodies, PRX002 23,72,73 and MEDI1341 74 that bind to total α-syn, have exhibited efficacy in ameliorating the disease phenotype of PD models when administered extracellularly, and they are currently in Phase II (ID: NCT03100149) and Phase I (ID: NCT04449484) clinical trial, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of pathologic αS requires cellular uptake, the induction of aggregation of a physiologic population of αS, and the release of newly generated pathologic αS. Multiple cellular receptors have been described for αS fibril spread, including heparan sulfate proteoglycans, TLR2, neurexins, Na + /K + -ATPase subunit α3, Lag3, Aplp1, FcγRIIb, and the cellular prion protein [ 2 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. The transmission of αS oligomers via an exosomal route has also been described, although there are conflicting reports regarding whether this exosomal pathway contributes to disease progression or is protective by reducing the intracellular pathologic αS burden when the capacity of the degradation machinery has been exceeded [ 70 , 71 , 72 , 73 ].…”
Section: Pathologic αSmentioning
confidence: 99%
“…Regardless, receptor-mediated αS fibril transmission appears to play a vital role in the disease process. This is suggested by evidence that two neuronally expressed αS fibril receptors, Lag3 and Aplp1, form a complex crucial for αS uptake and the knockout of either receptor substantially reduces pathologic αS spread, with double knockout largely sparing dopaminergic neurons in vivo [ 2 , 67 , 68 , 69 ]. Mechanistically, receptor binding is driven by electrostatic interactions between the acidic C-terminal region of αS fibrils and basic regions of the Lag3 D1 and Aplp1 E1 domains [ 67 ].…”
Section: Pathologic αSmentioning
confidence: 99%